The Application Value of the Renal Region of Interest Corrected by Computed Tomography in Single-Kidney Glomerular Filtration Rate for the Evaluation of Patients With Moderate or Severe Hydronephrosis - Yin, Haixia; Liang, Wenli; Zhao, Deshan (Frontiers in Physiology, 2022)
Objective: This study aimed to investigate the application value of the renal region of interest (ROI) corrected by computed tomography (CT) in single-kidney glomerular filtration rate (GFR) in patients with hydronephrosis. Methods: A total of 46 patients with hydronephrosis were divided into four groups based on their degree of unilateral hydronephrosis: a normal group (left kidney and right kidney) and three abnormal groups (mild, moderate, and severe hydronephrosis). GFR was measured using the two-sample method (tGFR). The single-kidney GFR of each patient was derived from differential renal function values in dynamic renal imaging multiplied by GFR. The single-kidney GFRs, including GFR from the Gates method (gGFRsingle) and CT area-corrected GFR (aGFRsingle), were compared with tGFRsingle. A paired-sample t-test and Pearson’s test were used for data analysis. p < 0.05 was considered statistically significant. Results: There were no significant differences between aGFRsingle and tGFRsingle in patients in the normal, mild hydronephrosis, and moderate hydronephrosis groups (t = –0.604∼1.982, all p > 0.05), but there was a significant difference between them in the severe hydronephrosis group (t = 2.302, p < 0.05). There were no significant differences between gGFRsingle and tGFRsingle in the normal and mild hydronephrosis groups (t = 0.194∼0.962, all p > 0.05), but there was a significant difference between them in the moderate and severe hydronephrosis groups (t = 3.321, 3.494, p < 0.05). Both gGFRsingle and aGFRsingle were correlated with tGFRsingle, with aGFRsingle being more strongly correlated (r = 0.890, p < 0.001). Conclusion: In patients with moderate hydronephrosis, aGFRsingle is more strongly correlated with tGFRsingle than gGFRsingle. However, in patients with severe hydronephrosis and accompanying renal morphological changes, the aGFRsingle measured by the renal ROI area-correction method using CT has higher accuracy and better clinical application value than the conventional gGFRsingle.